The Doctor Blake mysteries. Season one [videorecording (DVD)] - McLachlan, Craig, 1965-; Garner, Nadine; Tobeck, Joel, 1971- (BBC Worldwide Americas, Inc., 2015)
In 1959, Dr. Lucian Blake returns to his Australian hometown to continue his late father's medical practice, but it is his additional responsibility as the town's chief medical officer that leads him to investigating cases of suspicious death.